2021
DOI: 10.3390/antiox10101624
|View full text |Cite
|
Sign up to set email alerts
|

Histochrome Attenuates Myocardial Ischemia-Reperfusion Injury by Inhibiting Ferroptosis-Induced Cardiomyocyte Death

Abstract: Reactive oxygen species (ROS) and intracellular iron levels are critical modulators of lipid peroxidation that trigger iron-dependent non-apoptotic ferroptosis in myocardial ischemia-reperfusion (I/R) injury. Histochrome (HC), with a potent antioxidant moiety and iron-chelating capacity, is now available in clinical practice. However, limited data are available about the protective effects of HC on ferroptotic cell death in myocardial I/R injury. In this study, we investigated whether the intravenous administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 83 publications
(119 reference statements)
0
23
0
Order By: Relevance
“…With the surge of results confirming the pivotal role of ferroptosis in developing heart and liver diseases, some recent studies have demonstrated how targeting the ferroptotic pathway can be beneficial in inhibiting cell death induced by iron overload. For instance, the use of both iron chelator and antioxidants have been proposed as therapeutic tools in the treatment of myocardial infarction and in preconditioning the hearts of patients undergoing reperfusion manoeuvres [ 135 ]. In liver, several physiopathological pathways can be affected by impaired iron homeostasis including alcohol-induced hepatotoxicity [ 136 ], acute liver failure [ 85 ], drug-induced liver injury [ 137 ], and hepatic fibrosis [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the surge of results confirming the pivotal role of ferroptosis in developing heart and liver diseases, some recent studies have demonstrated how targeting the ferroptotic pathway can be beneficial in inhibiting cell death induced by iron overload. For instance, the use of both iron chelator and antioxidants have been proposed as therapeutic tools in the treatment of myocardial infarction and in preconditioning the hearts of patients undergoing reperfusion manoeuvres [ 135 ]. In liver, several physiopathological pathways can be affected by impaired iron homeostasis including alcohol-induced hepatotoxicity [ 136 ], acute liver failure [ 85 ], drug-induced liver injury [ 137 ], and hepatic fibrosis [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hearts of rats administered early intravenous injections of HC before reperfusion exhibited remarkably reduced cardiac fibrosis and increased capillary density. By inducing the expression of NRF2 and antioxidant genes, HC can reduce cytoplasmic and mitochondrial ROS, maintain intracellular GSH levels, and enhance GPX4 activity [ 75 ]. Wang et al demonstrated that myocardial infarction was substantially reduced by dexmedetomidine (Dex), and heart function improved, along with diminished lipid peroxidation and Fe 2+ accumulation.…”
Section: Mechanisms and Targeted Therapies For Ferroptosis In Irimentioning
confidence: 99%
“…Nevertheless, it also causes further myocardial damage ( Virani et al, 2020 ; Ren et al, 2021 ). MIRI is characterized by metabolic disturbance, cardiac dysfunction, inflammatory reaction, and cell death (apoptosis, autophagy, necrocytosis, pyroptosis, ferroptosis) ( Moens et al, 2005 ; Eltzschig and Eckle, 2011 ; Hwang et al, 2021 ; Lv et al, 2021 ; Peng et al, 2021 ).…”
Section: Myocardial Cell Apoptosis In Myocardial Ischemia/reperfusion...mentioning
confidence: 99%